Penggunaan Media Video Pembelajaran Berbasis Cerita Rakyat Manokwari terhadap Motivasi Belajar Bahasa Indonesia Murid Kelas I - Ernawati Alan Saputri; Yektiningtiyas, Wigati; Rahayu, Budi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
First-grade elementary school students have unique developmental characteristics, being active and having a high sense of curiosity, which makes it difficult to maintain attention during verbal-only lectures. This study aims to describe and analyze the use of Manokwari folklore-based instructional video media on Indonesian language learning motivation for 1st-grade students. This research employed a qualitative descriptive approach at SD Inpres 07 Kampung Ambon, Manokwari, with 26 students as subjects. Data collection techniques included observation, interviews, and documentation, analyzed through data reduction, data presentation, and conclusion drawing. The results indicated that the use of video media based on Mansinam Island folklore successfully increased students' attention, involvement, courage, and self-confidence during the learning process. Students were more focused while watching the videos, actively answered questions, were able to retell the lesson content, and responded positively to local culture-based materials. Interview results showed that the local context made students feel closer and more comfortable, facilitating their understanding of the material. Consequently, local folklore-based instructional video media is proven effective in increasing Indonesian language learning motivation for 1st-grade elementary school students.